Моделювання елементів і складових одиниць в системах оборотного водопостачання - Мовчан, Сергій Іванович; Мовчан, Сергей Иванович; Movchan, Serhii; Дереза, Олена Олександрівна; Дереза, Елена Александровна; Dereza, Olena; Дереза, Сергій Володимирович; Дереза, Сергей Владимирович; Dereza, Serhii (ТДАТУ, 2020)
UK: Розглянуто питання моделювання окремих елементів і складових одиниць, яке використовується в системах водопостачання. Системи господарсько-питного водопостачання, системи оборотного й повторно-обівого використання води є важливою галузю водогосподарського комплексу країни. Від раціонального вибору гідавлічних параметрів і характеристик трубопроводів, запірно-регулюючої арматури, напірно-регулюючих споруд і резервуарів залежить надійна і безперебійна робота будь-якої системи. Вирішення багатьох задач і експлуатаційних характеристик в роботі систем водопостачання можливо передбачити вже на стадії проєктування з використанням сучасних засобів і методів програмування, моделювання і прогнозування. Саме моделювання окремих елементів і складових одиниць систем водопостачання вирішить не лише практичну задачу продовження строку експлуатації вищеозначених систем, а й дозволить оптимізувати економічні показники при експлуаації переважної більшості систем використання і розподілення води на об’єктах водогосподарського призначення. RU: Рассмотрены вопросы моделирования отдельных элементов и сборочных единиц, которое используется в системах водоснабжения. Системы хозяйственно-питьевого водоснабжения, системы оборотного и повторно-обивого использования воды является важной отраслью водохозяйственного комплекса страны. От рационального выбора гидавличних параметров и характеристик трубопроводов, запорно-регулирующей арматуры, напорно-регулирующих сооружений и резервуаров зависит надежная и бесперебойная работа любой системы. Решение многих задач и эксплуатационных характеристик в работе систем водоснабжения возможно предусмотреть уже на стадии проектирования с использованием современных средств и методов программирования, моделирования и прогнозирования. Именно моделирования отдельных элементов и сборочных единиц систем водоснабжения решит не только практическую задачу продления срока эксплуатации вышеуказанных систем, но и позволит оптимизировать экономические показатели при експлуаации подавляющего большинства систем использования и распределения воды на объектах водохозяйственного назначения. EN: The issue of modeling of separate elements and constituent units, which is used in water supply systems, is considered. Systems of economic and drinking water supply, systems of circulating and repeated water use are an important branch of the water management complex of the country. Reliable and uninterrupted operation of any system depends on a rational choice of hydraulic parameters and characteristics of pipelines, shut-off and regulating fittings, pressure-regulating constructions and tanks. The solution of many problems and operational characteristics in the work of water supply systems can be predicted at the design stage using modern tools and methods of programming, modeling and forecasting. It is the modeling of individual elements and components of water supply systems that will solve not only the practical problem of extending the service life of the above systems, but also allow optimizing economic performance in the operation of the vast majority of water use and distribution systems. Increasing the cost of water, energy and other consumables requires careful attention to the design, development and further improvement of individual elements for their modeling using modern technologies. The most convenient for creating models of mixers of aqueous solutions is solid modeling. Types, sections, sections of the model, animation provide an opportunity to visualize the processes that occur when mixing aqueous solutions and reagents in the middle of the equipment. Creating solid models is more important than ever today, as it allows you to quickly create an object and edit it just as quickly. The speed of modeling has a positive effect on the rate of return on investment, which is very important in optimizing the quantitative and qualitative composition of water in circulating water supply systems.
Моделирование элементов и сборочных единиц в системах оборотного водоснабжения
Simulation of elements and component units in reverse water supply systems
Keywords: системи оборотного водопостачання; гідравлічний опір; змішувач водних розчинів; 3D-моделювання; твердотільне моделювання; системы оборотного водоснабжения; гидравлическое сопротивление; смеситель водных растворов; 3D-моделирование; твердотельное моделирование; circulating water supply systems; hydraulic resistance; mixer of aqueous solutions; 3D modeling; solid modeling